Adults still can't resist: A social robot can induce normative conformity. (February 2022) - Qin, Xin; Chen, Chen; Yam, Kai Chi; Cao, Limei; Li, Wanlu; Guan, Jian; Zhao, Puchu; Dong, Xiaowei; Lin, Yiqiang
Abstract: Social robots are widely used in many areas of our work and life. Vollmer et al. (2018) recently provided initial evidence that while adults could resist the pressure to conform to social robots, children could not. However, we suggest that these findings are incomplete because they investigated a setting in which single individuals were paired with a group of robot peers. In this research, we investigate the more likely scenario in which social robots represent the minority in human-robot interactions. Using the classic Asch paradigm, we reveal that a single social robot as a member of group does elicit normative conformity. We further explore whether positioning robots as dissenters can reduce conformity. We find that a social robot who dissents with the correct answer has a comparable, albeit weaker, effect on reducing conformity and increasing accuracy as a human dissenter, whereas a social robot who dissents with another incorrect answer decreases conformity but does not increase accuracy. These results suggest that social robots can and do influence normative conformity, with significant ethical and practical implications. Highlights: We investigate the more likely scenario in which social robots represent the minority in human-robot interactions. Using the classic Asch paradigm, we find that a social robot as a member of group does elicit normative conformity. A social robot who dissents a correct answer reduces conformity and increases accuracy. A social robot who dissents with another incorrect answer decreases conformity but does not increase accuracy.